2004
DOI: 10.1016/s0001-2092(06)60689-3
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Computer Game to Prepare Children for Surgery

Abstract: Computer games are a major part of the culture of children and teenagers in many developed countries. Research shows that children of the computer age prefer computer-assisted learning to any other teaching strategy. Health care workers traditionally have used dolls, games, drawings, creative arts, and even videotapes to prepare children for surgery. No studies have been conducted in Israel on using computers to help ailing children in general or to help children preparing for surgery in particular. This artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 12 publications
0
27
0
3
Order By: Relevance
“…A variety of formats have been examined for preparation, such as computer programs, 26 videos, 27,28 puppets, 29 written summaries, 30 and live models. 31 Typically, the formats combine some diversion along with didactics and experiential learning.…”
Section: Formatmentioning
confidence: 99%
“…A variety of formats have been examined for preparation, such as computer programs, 26 videos, 27,28 puppets, 29 written summaries, 30 and live models. 31 Typically, the formats combine some diversion along with didactics and experiential learning.…”
Section: Formatmentioning
confidence: 99%
“…Several studies have highlighted the relevant role of using video games to help patients cope with surgery (Patel et al, 2006;Rassin et al, 2004). Patel and colleagues (2006) analysed the effect of video games on cognitive distraction in children undergoing surgery, and showed its efficacy in reducing anxiety in both the preoperative and the perioperative phases.…”
mentioning
confidence: 99%
“…The use of video games as an educational tool to prepare children to cope with surgical processes and medical procedures has also been analysed, but few studies have evaluated their effects. To our knowledge, only one published work (Rassin et al, 2004) has reported on the development of a video game for elementary school-aged children to help them cope with surgical processes and medical procedures but limited its scope to tonsillectomy and adenoidectomy surgeries.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Par ailleurs, certains auteurs se montrent prudents au sujet de l'efficacité de ce moyen pour l'apprentissage ou le changement d'attitudes en matière de santé (Rassin, Gutman et Silner, 2004 ;Barab et al, 2005 ;Baldaro et al, 2004).…”
Section: éDucation à La Santé : Efficacité Des Jeux éDucatifs Numériquesunclassified